NCAPH promotes cell proliferation and inhibits cell apoptosis of bladder cancer cells through MEK/ERK signaling pathway. Issue 4 (16th February 2022) - Li, Bo; Xiao, Qian; Shan, Liping; Song, Yongsheng
ABSTRACT: Bladder cancer (BC) is one of the most common cancers world-wide with a poor prognosis. Non-SMC (Structural Maintenance of Chromosomes)-condensin I complex subunit H (NCAPH) is a regulatory subunit of the condensin I complex and plays an important role in tumorigenesis and progression in several types of cancers. However, the role of NCAPH in BC remains unknown. In this study, we tried to reveal the biological functions of NCAPH in BC. We detected the expressions of NCAPH in BC and adjacent tissues, and BC cells lines. Subsequently, the gain- and loss-of-function experiments were performed to determine the effects of NCAPH on BC cell proliferation, apoptosis, and activation of the MEK/ERK signaling pathway in vitro. Moreover, we used BALB/c nude mice and established a xenograft model to investigate whether silence NCAPH using shRNA targeting NCAPH (shNCAPH) can inhibit BC tumor growth in vivo. The results showed NCAPH was overexpressed in BC tissues compared to adjacent tissues and highly expressed in BC cell lines. Additionally, overexpression of NCAPH promoted cell proliferation and inhibited apoptosis in SW780 cells. Conversely, knockdown of NCAPH reduced cell proliferation and enhanced apoptosis in UMUC3 cells. Furthermore, we found that the NCAPH activated the MEK/ERK signaling pathway in BC cells. MEK1/2 inhibitor U0126 blocked the increase of cell proliferation regulated by NCAPH overexpression. Knockdown of NCAPH significantly inhibited tumor growth in mice. Our results suggest that NCAPH might play an important role in BC progression and provide the potential marker in the diagnosis of BC.